Design, synthesis, and anticonvulsant effects evaluation of nonimidazole histamine H3 receptor antagonists/inverse agonists containing triazole moiety. (1st January 2020) - Song, Mingxia; Yan, Rui; Zhang, Yanhui; Guo, Dongfu; Zhou, Naiming; Deng, XianQing
Abstract: Histamine H3 receptors (H3 R) antagonists/inverse agonists are becoming a promising therapeutic approach for epilepsy. In this article, novel nonimidazole H3 R antagonists/inverse agonists have been designed and synthesised via hybriding the H3 R pharmacophore (aliphatic amine with propyloxy chain) with the 1, 2, 4-triazole moiety as anticonvulsant drugs. The majority of antagonists/inverse agonists prepared here exerted moderate to robust activities in cAMP-response element (CRE) luciferase screening assay. 1-(3-(4-(3-Phenyl-4 H -1, 2, 4-triazol-4-yl)phenoxy)propyl)piperidine (3l ) and 1-(3-(4-(3-(4-chlorophenyl)-4 H -1, 2, 4-triazol-4-yl)phenoxy)propyl)piperidine (3m ) displayed the highest H3 R antagonistic activities, with IC50 values of 7.81 and 5.92 nM, respectively. Meanwhile, the compounds with higher H3 R antagonistic activities exhibited protection for mice in maximal electroshock seizure (MES)-induced convulsant model. Moreover, the protection of 3m against the MES induced seizures was fully abrogated when mice were co-treated with RAMH, a CNS-penetrant H3 R agonist, which suggested that the potential therapeutic effect of 3m was through H3 R. These results indicate that the attempt to find new anticonvulsant among H3 R antagonists/inverse agonists is practicable.